2001
DOI: 10.1002/nme.246
|View full text |Cite
|
Sign up to set email alerts
|

In‐plane vibrations of shear deformable curved beams

Abstract: SUMMARYThis paper presents the exact dynamic sti ness matrix for a circular beam with a uniform cross-section. The sti ness matrix is frequency dependent, and the natural frequencies are those that cause the matrix to become singular. Using this matrix the exact natural frequencies of circular beams with various boundary conditions are calculated and compared with available results in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 14 publications
4
27
0
3
Order By: Relevance
“…It is observed that very close agreement exists between the present results and those published in Refs. [11,13,36]. The associated modal shapes are also presented in Fig. 14 where an excellent agreement is observed with the results given in Ref.…”
Section: The Non-dimensional Natural Frequencies ( Eisupporting
confidence: 87%
See 3 more Smart Citations
“…It is observed that very close agreement exists between the present results and those published in Refs. [11,13,36]. The associated modal shapes are also presented in Fig. 14 where an excellent agreement is observed with the results given in Ref.…”
Section: The Non-dimensional Natural Frequencies ( Eisupporting
confidence: 87%
“…The associated modal shapes are also presented in Fig. 14 where an excellent agreement is observed with the results given in Ref. [11]. It should be noted that in figures depicting the modal shapes, the horizontal axis represents the non-dimensional length parameter s/l in which, s is the tangential curvilinear coordinate and l is the total length of the beam.…”
Section: The Non-dimensional Natural Frequencies ( Eisupporting
confidence: 81%
See 2 more Smart Citations
“…In these cases, it is necessary to introduce a representation of the centroidal axis. Many papers refer to the circular arch case (see for example, [8][9][10][11]), while the case of arbitrarily curved geometry was afforded earlier using simple straight beams and later using B-splines [12] or cubic Hermite functions. In this work, a modified Hermitian elementwise cubic parametric description is adopted.…”
Section: Introductionmentioning
confidence: 99%